INOVASI PELAYANAN SUPERONE (SURAT PENGANTAR ONLINE) DI KECAMATAN CANDISARI KOTA SEMARANG - Usy Tiaranika; Maesaroh Maesaroh (Dialogue : Jurnal Ilmu Administrasi Publik, 2020)
There are many challenges and obstacles faced by the government in implementing public services until now. The emergence of public service problems must be resolved immediately in order to create good governance by applying E-Government. Based on the Regulation of the Mayor of Semarang, Candisari District, in this case, also runs the District Integrated Administration Service (PATEN) standard by making an innovation in the form of an online cover letter through an application called SUPERONE in order to achieve a fast, effective and efficient online-based service system. The purpose of this study is to analyze how the SUPERONE application innovation in Candisari District, Semarang City and to find out the inhibiting factors of the SUPERONE application innovation in Candisari District, Semarang City. The research design used in this research is qualitative research with descriptive research type. The results of this study, namely the SUPERONE application can solve public service problems, but in practice there are obstacles, namely there are still many people who do not know about the SUPERONE application, the lack of public knowledge in supporting this change project, the less maximal use of smartphones in the community in administering administrative services, lack of quality and the quantity of technical human resources in providing services, the absence of a mobile application (android) that supports administrative services.